Herbicide Strategies for Managing Glyphosate- and Dicamba-Resistant Kochia in Roundup Ready 2 Xtend Soybean - V. Kumar; R. Liu; T. Lambert; P. W. Stahlman (Kansas Agricultural Experiment Station Research Reports, 2019)
Kochia populations with multiple resistance to glyphosate and dicamba are an increasing concern for growers in the High Plains region, including Kansas. A field study was conducted at the Kansas State University Agricultural Research Center near Hays, KS, to evaluate and develop herbicide options for controlling glyphosate- and dicamba-resistant kochia in Roundup Ready 2 Xtend soybean. The study site was uniformly infested with a glyphosate- and dicamba-resistant kochia population prior to soybean planting. Fifteen herbicide treatments (programs), including PRE alone and PRE followed by (fb) POST-applied herbicides, were investigated in a randomized complete block design with four replications. All PRE treatments included Roundup PowerMax for control of other weed species. Results indicated that a single PRE application of Spartan alone or with Engenia, Panther PRO, and Zidua plus Valor SX provided season-long control of glyphosate- and dicamba-resistant kochia. A single PRE application of Engenia or Zidua alone only provided 70 to 78% kochia control at 6 weeks after POST (WAPOST) application. However, PRE-applied Zidua alone or with Engenia, Engenia alone, Spartan + Zidua, and Spartan + Sencor followed by a sequential POST application of a tank-mixture containing Engenia and Roundup PowerMax provided ≥ 95% kochia control at 6 WAPOST. Kochia biomass reduction was>92% with a majority of the treatments; exceptions were Zidua PRE alone (59% reduction), Engenia alone (76% reduction), and Zidua + Engenia (88% reduction) treatments. Soybean grain yield for a majority of the tested treatments did not differ, and ranged from 23 to 25 bu/a. These results suggest that effective PRE herbicide options are available for managing glyphosate- and dicamba-resistant kochia in Roundup Ready 2 Xtend soybean.
Keywords: glyphosate; dicamba; multiple resistant kochia; dicamba-tolerant soybean